Perancangan Analog Front End (AFE) untuk Akuisisi Isyarat EKG - Enas Dhuhri Kusuma; Fikri Zaini Baridwan; Indah Soesanti (Institut Teknologi Adhi Tama Surabaya, 2023)
Electrocardiogram or ECG is a curve representing electrical activity of the heart. ECG recorder generally consists of analog front end (AFE) and microcontroller for analog signal acquisition, signal processing and data transmission. As a signal conditioner, AFE is the most important part of an ECG recorder. With AFE, ECG signal with 1mV magnitude and interfered, will be conditioned to a microcontroller readable signal by its analog input. Proposed AFE is an electronic circuit with two main functions: amplifier and filtering. The filter uses second order Sallen-Key configuration. Proposed AFE uses two main components: operational amplifier and instrumentation amplifier. The device is able to amplify ECG signals with 66 dB gain or 1800V/V so a signal with 1mV magnitude will be able to be conditioned into a microcontroller compatible signal. CMRR of the proposed device is 79.9 dB with SNR 30 dB.